(untitled) (Andamios, Revista de Investigación Social, 2006)
The present article raises some lines of discussion and reflection from the necessity of paying attention to the problematic one from access Andamios 325 ABSTRACTS the university. This is an increasing concern in the Higher Education agenda in Latin America. Two positions that appear in this discussion: the restricted admission which emphases the preservation of high patterns of academic excellence through the selectivity of future students, and the second position that defends the unrestricted and direct admission that prioritizes equality criteria. A basic aim of the educational policies lays upon the postulation of increasing the register list, as promoter of equal opportunity and at the same time, the attempt to achieve educational excelence. Is this possible in the context of the LatinAmerican countries?